Neurophysiology and readiness, rather than mental toughness and grit - Sullivan, J. (MindzFeed, 2017)
Finding ways in which athletes can be ready for the demands of sport training and competition is paramount for success. The scope of this summary will clarify the importance of why we need to depart from concepts of `mental toughness` and `grit` and, instead, focus on understanding neurophysiology and readiness to create opportunities for managing athlete health and performance throughout cycles of training and competition.